2019
DOI: 10.1152/ajpcell.00507.2018
|View full text |Cite
|
Sign up to set email alerts
|

Volume-regulated Cl current: contributions of distinct Cl channels and localized Ca2+ signals

Abstract: The swelling-activated chloride current ( ICl,swell) is induced when a cell swells and plays a central role in maintaining cell volume in response to osmotic stress. The major contributor of ICl,swell is the volume-regulated anion channel (VRAC). Leucine-rich repeat containing 8A (LRRC8A; SWELL1) was recently identified as an essential component of VRAC, but the mechanisms of VRAC activation are still largely unknown; moreover, other Cl− channels, such as anoctamin 1 (ANO1), were also suggested to contribute t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…LRRC8 family members are the molecular correlates of VRAC, and LRRC8A constitutes an essential subunit which co-assembles with one or more other LRRC8 member(s) to give rise to VRAC (Qiu et al, 2014;Voss et al, 2014). DRG neurons express mRNA transcripts encoding LRRC8A and a VRAC current can be induced both by hypotonic extracellular solution as well as by hypertonic pipette solution suggesting that LRRC8A contributes to VRAC in DRG neurons, albeit a role in nociception has not been shown unequivocally (Wang et al, 2017;Liu et al, 2019). Interestingly, Ca 2+ -activated Cl − channels might contribute to VRAC: Ano1 can also be activated by cell swelling and members of the tweety-homolog family (see Ca 2+ -activated Cl − channel section) constitute essential subunits for swelling-induced VRAC in cultured cortical astrocytes (Han et al, 2019;Liu et al, 2019).…”
Section: Volume-regulated Anion Channels (Vrac or Vsoac)mentioning
confidence: 99%
See 1 more Smart Citation
“…LRRC8 family members are the molecular correlates of VRAC, and LRRC8A constitutes an essential subunit which co-assembles with one or more other LRRC8 member(s) to give rise to VRAC (Qiu et al, 2014;Voss et al, 2014). DRG neurons express mRNA transcripts encoding LRRC8A and a VRAC current can be induced both by hypotonic extracellular solution as well as by hypertonic pipette solution suggesting that LRRC8A contributes to VRAC in DRG neurons, albeit a role in nociception has not been shown unequivocally (Wang et al, 2017;Liu et al, 2019). Interestingly, Ca 2+ -activated Cl − channels might contribute to VRAC: Ano1 can also be activated by cell swelling and members of the tweety-homolog family (see Ca 2+ -activated Cl − channel section) constitute essential subunits for swelling-induced VRAC in cultured cortical astrocytes (Han et al, 2019;Liu et al, 2019).…”
Section: Volume-regulated Anion Channels (Vrac or Vsoac)mentioning
confidence: 99%
“…DRG neurons express mRNA transcripts encoding LRRC8A and a VRAC current can be induced both by hypotonic extracellular solution as well as by hypertonic pipette solution suggesting that LRRC8A contributes to VRAC in DRG neurons, albeit a role in nociception has not been shown unequivocally (Wang et al, 2017;Liu et al, 2019). Interestingly, Ca 2+ -activated Cl − channels might contribute to VRAC: Ano1 can also be activated by cell swelling and members of the tweety-homolog family (see Ca 2+ -activated Cl − channel section) constitute essential subunits for swelling-induced VRAC in cultured cortical astrocytes (Han et al, 2019;Liu et al, 2019). As mRNA transcripts encoding Ttyh1/2/3 are apparently abundant in lumbar DRGs, and as expression levels of Ttyh1 appear to be slightly regulated in axotomized DRG neurons, it is tempting to speculate that tweety proteins may contribute to VRAC currents in DRG neurons (L4/L5; Al-Jumaily et al, 2007;Boudes et al, 2009).…”
Section: Volume-regulated Anion Channels (Vrac or Vsoac)mentioning
confidence: 99%
“…However, other authors recently showed that low ionic strength is neither sufficient to activate VRAC on intracellular compartments, nor indispensable to keep plasma membrane-localized VRACs active, and rather suggested that the diacylglycerol/protein kinase D pathway specifically and potently activates VRAC 52 . Therefore, in a cellular context, other factors, including binding partners, post-translational modifications 53 , second messengers or even other channels 54 , may contribute to VRAC activation besides a mere reduction in the intracellular ionic strength.…”
Section: Discussionmentioning
confidence: 99%
“…For example, VRAC activation caused by swelling can activate other Cl - channels, notably anoctamin 1 (e.g. Liu et al, 2019 ; Benedetto et al, 2016 ). Furthermore, whilst our research suggests an importance of Cl - , VRAC is also permeable to small molecules including cGAMP ( Zhou et al, 2020 ) and ATP ( Dunn et al, 2020 ), highlighting additional ways through which VRAC could contribute to inflammation.…”
Section: Discussionmentioning
confidence: 99%